A construção de um microtesauro brasileiro de educação a distância à luz da Teoria Comunicativa da Terminologia - Ferreira, Raquel Ellen Simões (2023)
Distance Education (DE) is a teaching modality that has experienced significant growth, with research in this field being driven especially by the COVID-19 pandemic. However, it has been observed that the terminological field of DE presents conceptual divergences and terminological conflicts, which hinder communication and research in this context. Therefore, this master's research was justified by the need to assist DE participants through the analysis and control of the specific language of this educational modality. In light of this, this research proposes the construction of a micro-thesaurus for DE based on the Communicative Theory of Terminology, aiming to achieve a common and clear language for the representation of specialized knowledge. The research objectives are to understand the contributions of the Communicative Theory of Terminology to Knowledge Representation, relate these contributions to the thesaurus construction process, and develop a micro-thesaurus for DE. The research adopts a qualitative approach and uses an exploratory study through bibliographic and documentary research for theoretical discussion of relevant topics. The methodology adopted for the construction of the micro-thesaurus involves term selection and mapping through a concept map, followed by the structuring of concepts through terminological records. The thesaurus was built using the TemaTres software, following the stages of Cervantes' integrated model for thesaurus construction. The results reveal a comprehensive view of DE, highlighting the importance of thesauri as terminological control tools. The developed micro-thesaurus provides a valuable starting point for future expansions and enhancements. Prospects for future work include validation, continuous updating, and practical applications of the micro-thesaurus.